Efficacy and safety of angiotensin II receptor type 1 antagonists in children and adolescents - Herder, Siegtraut Dorothea; Weber, Ernst; Winkemann, Almuth; Herder, Christoph; Morck, Hartmut (Pediatric nephrology, 2010)
Our purpose was to evaluate the effects of angiotensin II receptor type 1 antagonists (ARAs) in children and adolescents with hypertension or/and several kinds of nephropathies on blood pressure (BP) and proteinuria and to evaluate related safety issues. Data sources were Medline, Embase, The Cochrane Library, BIOSIS Previews, contact with investigators and manufacturers, personal bibliography of the lead author, and manual searches. We selected randomized controlled trials (RCTs), uncontrolled trials, and case series investigating ARAs in children and adolescents, as well as case reports about adverse events and the embryotoxic effects of ARAs in children. In four RCTs with 698 individuals, mean systolic blood pressure (BP) decreased by 10.5 mmHg [95% confidence interval (CI) 9.8−11.2] and mean diastolic BP by 6.4 mmHg (95% CI 5.8−7.0). Proteinuria decreased by 30−64% (range) in two RCTs and four case series. Safety data were comparable with adult safety data. ARAs can be considered effective and safe in lowering BP and proteinuria in the pediatric age group. The correlation between the surrogate parameters BP and proteinuria with clinical end points is documented to a large degree. The evidence is based on RCTs and also on lower evidence levels, such as case series. In some conditions, RCTs in children are not feasible. Registers could provide more evidence in the future.